Enhancing Islamic Religious Education Learning Quality Through Principal Policy: Evidence from an Island-Based Secondary School - Muhammad Rizal Toyo; Farid Ma’ruf Rumadaul (IAIN Ambon, 2024)
This study aims to analyze the policies implemented by school principals in improving the quality of Islamic Religious Education (IRE) learning at a senior high school located in a remote island area of Indonesia. The research employed a qualitative case study approach to gain an in-depth understanding of leadership practices and policy implementation in the educational setting. Data were collected through interviews, observations, and document analysis involving the principal, Islamic Religious Education teachers, and relevant school stakeholders. The data were analyzed using the stages of data reduction, data display, and conclusion drawing.The findings reveal that the principal plays a strategic role in enhancing the quality of IRE learning through several policy initiatives, including strengthening teacher professionalism, providing continuous academic supervision, supporting the integration of religious values into school culture, improving learning facilities, and encouraging innovative teaching methods. These policies contributed to better instructional practices, increased student participation, and the creation of a more conducive religious learning environment. Despite challenges such as limited educational resources and geographical constraints, the principal’s commitment and leadership were found to be significant factors in maintaining and improving the quality of Islamic Religious Education. The study concludes that effective principal policies and instructional leadership are essential for fostering quality learning outcomes, particularly in schools located in remote and disadvantaged regions